Transformasi Media Sosial sebagai Lingkungan Pendidikan Islami yang Mendorong Literasi dan Pemikiran Kritis - Elia, Elia Nur Rohmah; Zahratusshiefa, Apriliana Nayla; Saputra, Dewa Satria; Syaifuddin, Mohammad (Jurnal Pendidikan Islam, 2025)
This study aims to analyze the transformation of social media as a space for Islamic education in the digital era by highlighting the role of platforms such as YouTube, Instagram, TikTok, and X (Twitter) as learning environments that instill Islamic values, enhance digital literacy, and foster critical thinking among young Muslims. Using a qualitative descriptive method with a phenomenological approach, this research explores the meaning and dynamics of digital da’wah through literature review and non-participant observation of popular Islamic accounts, which were then analyzed thematically following the stages of data reduction, presentation, and conclusion drawing. The results indicate that social media has evolved from merely a medium of communication and entertainment into a non-formal educational space rich in moral, spiritual, and intellectual values. The success of social media as an Islamic educational environment is determined by the credibility of its scholarly sources, the application of ethical and courteous online behavior, and the active participation of digital learning communities. The integration of Islamic values with digital literacy is the key to maintaining the digital sphere as an ethical, educational, and productive space. This study concludes that social media holds great potential as a transformative ecosystem for Islamic education when managed strategically and based on the principle of iqra’, as stated in Surah Al-‘Alaq [96]: 1–5. Consequently, Islamic education in the digital era serves not only as a means of knowledge transfer but also as a process of shaping character, critical awareness, and moral responsibility among Muslim youth amid the complexities of global information flows.